Post traumatic stress disorder and the forensic radiographer. Issue 3 (August 2016) - Glaysher, E.; Vallis, J.; Reeves, P.
Abstract: The term post traumatic stress disorder (PTSD) is used to describe the psychological issues resulting from any traumatic event. An individual's ability to function is impaired by experiencing emotional responses to a traumatic event. Forensic radiographers need to be aware of the potential debilitating effects of this condition and those writing forensic protocols must take the condition into account and build in safeguards and welfare strategies. This narrative review looks at the origins of the term PTSD and highlights those who may be at increased risk of developing the condition including, in particular, forensic radiographers involved in mass fatality work. Signs, symptoms and possible treatments are also reviewed. Highlights: Presents a summary of PTSD for those working in forensic radiography. Outlines signs & symptoms of PTSD. Discusses treatment & prognosis of PTSD. Suggests ways of managing factors which may predispose to PTSD.